CFD simulation of bubbling fluidized bed: Effect of distributor plate orifice pattern configuration on hydrodynamics of gas-solid mixing - Afrooz, I.E. (Asian Research Publishing Network, 2016)
The gas-solid mixing pattern in a fluidized bed is significantly affected by distributor plates. In order to study this impact, two different distributer plates orifice arrangement, namely, triangular and radial (TDP and RDP) are designed. The solid circulation patterns caused by each orifice arrangements are then predicted numerically. To this end, Eulerian-Eulerian (EE) approach through Computational Fluid Dynamic (CFD) is utilized. As a final point, the simulated particle volume fraction, particle velocity and bed pressure drop are compared. It was found that the distribution of solid volume fraction is more homogeneous while TDP was used. The regular pattern of radial particle velocity was also found for TDP. These indicate that particle motion mainly concentrates in the region between the core and the wall of the bed. However, chaotic solid motion at the core region was observed for RDP. Â©2006-2016 Asian Research Publishing Network (ARPN).